Some Generalizations of Frames in Hilbert Modules - Mohamed Rossafi; Samir Kabbaj (International Journal of Mathematics and Mathematical Sciences)
Frames play significant role in various areas of science and engineering. In this paper, we introduce the concept of frames for the set of all adjointable operators from ℋ to K and their generalizations. Moreover, we obtain some new results for generalized frames in Hilbert modules.